(untitled) (Medical Forum Monthly, 2024)
Objective: Aim of the study was to investigate the prevalence of diabetes and HIV infection by screening in newly diagnosed pulmonary tuberculosis patients. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Pulmonology Department of Shahida Islam Medical College, Lodhran from 10 June 2016 to 10 June 2017. Materials and Methods: This study was conducted after taking approval from the institutional ethical committee. Total 159 newly diagnosed pulmonary tuberculosis patients were recruited by non-probability consecutive sampling. Mean and SD was calculated for numerical variables like age, BMI, fasting blood glucose (FBG), Hemoglobin and monthly income. Frequency and percentages were calculated for categorical variables like gender, smoking status, educational status, alcohol consumption, prevalence of HIV and diabetes, Ch square test was use to check significant different in PTB and Non PTB patients. P value of <0.05 was taken as significant. Results: Significant difference was found between age (p=0.000), BMI (p=0.000), FBG (p=0.000), hemoglobin (p=0.000), gender (p=0.002) and alcohol consumption (p=0.034), in groups, except education status (p=0.090) and monthly income (p=0.068). The main outcome variables of this study were HIV infection and diabetes. HIV infection was noted in 3.1% (n=5) and 1.9% (n=3) patients for PTB and non-PTB group respectively. While, 8.2% (n=13) and 4.4% (n=4) patients suffered from diabetes, for both the groups respectively. Conclusion: The results of our study revealed that on screening of newly diagnosed pulmonary tuberculosis patients with HIV infection and diabetes, their prevalence was high as compared to non-pulmonary tuberculosis group. But this difference was statistically non significant (P value 0.474 and 0.166).